Leaf transcriptome profiling of contrasting sugarcane genotypes for drought tolerance under field conditions - Contiliani, Danyel Fernandes; de Oliveira Nebó, João Felipe Carlos; Ribeiro, Rafael Vasconcelos; Andrade, Larissa Mara; Peixoto Júnior, Rafael Fávero; Lembke, Carolina Gimiliani; Machado, Ricardo Silverio; Silva, Daniel Nunes; Belloti, Mariana; de Souza, Gláucia Mendes; Perecin, Dilermando [UNESP]; Pereira, Tiago Campos; et al. (Springer Nature, 2022)
Drought is the most detrimental abiotic stress to sugarcane production. Nevertheless, transcriptomic analyses remain scarce for field-grown plants. Here we performed comparative transcriptional profiling of two contrasting sugarcane genotypes, ‘IACSP97-7065’ (drought-sensitive) and ‘IACSP94-2094’ (drought-tolerant) grown in a drought-prone environment. Physiological parameters and expression profiles were analyzed at 42 (May) and 117 (August) days after the last rainfall. The first sampling was done under mild drought (soil water potential of −60 kPa), while the second one was under severe drought (soil water potential of −75 kPa). Microarray analysis revealed a total of 622 differentially expressed genes in both sugarcane genotypes under mild and severe drought stress, uncovering about 250 exclusive transcripts to ‘IACSP94-2094’ involved in oxidoreductase activity, transcriptional regulation, metabolism of amino acids, and translation. Interestingly, the enhanced antioxidant system of ‘IACSP94-2094’ may protect photosystem II from oxidative damage, which partially ensures stable photochemical activity even after 117 days of water shortage. Moreover, the tolerant genotype shows a more extensive set of responsive transcription factors, promoting the fine-tuning of drought-related molecular pathways. These results help elucidate the intrinsic molecular mechanisms of a drought-tolerant sugarcane genotype to cope with ever-changing environments, including prolonged water deficit, and may be useful for plant breeding programs.